Carbon-nitrogen coupling on Pt(111) and its relevance to the catalytic synthesis of HCN - Herceg, Eldad; Trenary, Michael (Ciencia, 1970)
The surface chemistry of carbon-nitrogen coupling is of fundamental importance to the industrial- scale catalytic synthesis of HCN from CH4 and NH3 over Pt gauze catalysts. In order to elucidate the details of the synthesis, we investigated the mechanism of CN bond formation on Pt(111) with reflection absorption infrared spectroscopy (RAIRS) and temperature programmed desorption (TPD). The relevant surface intermediates were generated through the thermal decomposition of CH3I or C2H4 and the electron induced dissociation or oxydehydrogenation of NH3. The formation of surface CN is detected through HCN desorption at 500 K in theTPD experiments. The appearance of the vibrational features characteristic of the arninocarbyne (CNH2) species upon hydrogenation of surface CN at 300 K in the RAIR spectra has been used to establish the CN bond formation temperature. The RAIRS results indicate that HCN desorption at 500 K is kinetically limited by the formation of the CN bond at this temperature from surface C and N atoms. The formation of CN is suppressed in the presence of high coverages of surface carbon, in agreement with previous model reactor kinetic studies. In contrast, the coverage and overlayer structure of surface nitrogen has a negligible influence on the coupling reaction. Our results indicate that the high temperatures used in the industrial synthesis of HCN are needed primarily to activate methane and ammonia dissociative adsorption on the Pt catalyst surface.